2020
DOI: 10.1002/smll.202001343
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Fe–Mn Layered Double Hydroxides Nanosheets Anchored with Upconversion Nanoparticles for Oxygen‐Elevated Synergetic Therapy and Bioimaging

Abstract: Scheme 1. Schematic illustration for the formation and transport of UCSP-LDH in blood vessel, enhanced permeability and retention (EPR) mediated tumor accumulation, proposed PDT/PTT/CDT mechanism, and multiple imaging functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 83 publications
0
71
0
Order By: Relevance
“…[ 127 ] In recent studies, many 2D nanomaterials, such as GO, MoS 2 , MoSe 2 , Bi 2 Se 3 , and black phosphorus, have been explored for PTT of tumors mediated by near‐infrared light (NIR). [ 128–131 ] Liu et al. first reported that 2D ultrathin MnO 2 nanosheets, as novel photothermal agents, had essentially high photothermal conversion capacity for highly efficient PTT against tumor with ultra‐sensitivity to endogenous TME.…”
Section: The Synthesis Of Mn‐based Nanostructures For Bioimaging and Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 127 ] In recent studies, many 2D nanomaterials, such as GO, MoS 2 , MoSe 2 , Bi 2 Se 3 , and black phosphorus, have been explored for PTT of tumors mediated by near‐infrared light (NIR). [ 128–131 ] Liu et al. first reported that 2D ultrathin MnO 2 nanosheets, as novel photothermal agents, had essentially high photothermal conversion capacity for highly efficient PTT against tumor with ultra‐sensitivity to endogenous TME.…”
Section: The Synthesis Of Mn‐based Nanostructures For Bioimaging and Cancer Therapymentioning
confidence: 99%
“…[127] In recent studies, many 2D nanomaterials, such as GO, MoS 2 , MoSe 2 , Bi 2 Se 3 , and black phosphorus, have been explored for PTT of tumors mediated by near-infrared light (NIR). [128][129][130][131] Liu et al first reported that 2D ultrathin MnO 2 nanosheets, as novel photothermal agents, had essentially high photothermal conversion capacity for highly efficient PTT against tumor with ultra-sensitivity to endogenous TME. [73] Ultra-thin 2D MnO 2 nanosheets were prepared by chemical exfoliation, which was modified with soybean phospholipid (SP) via rotary evaporation technology, resulting in high stability in physiological solution (Figure 7).…”
Section: Mno 2 Nanosheetsmentioning
confidence: 99%
“…As an unusual anti-stokes process, photon upconversion (UC) refers to converting several low-energy photons to one high-energy photon ( Zhou et al, 2015 ; Wei et al, 2016 ). Due to the non-linear instincts, UC materials are well-developed for bio-imaging ( Gonzalez-Bejar et al, 2016 ; Chen et al, 2021 ), photo-dynamics therapy( Lucky et al, 2015 ; Liu et al, 2019 ; Jia et al, 2020 ), and single particle imaging ( Gargas et al, 2014 ; Liu et al, 2017 ; Zhou et al, 2020b ; Dong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, searching for integrated therapeutic strategies with multi-modal therapeutics is highly necessary to achieve remarkable antitumor effects. [8][9][10][11][12] The SDT and PDT have been selected as potential clinical methods for treating a wide range of superficial and localized tumors. They utilize the sono-irradiation or photoexcitation to generate highly reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ) and hydroxyl radicals (•OH).…”
mentioning
confidence: 99%